A Struggle to the Rights of Getting Islamic Religious Education at State Elementary Schools in North Minahasa - Mustafa Mustafa; Muh Idris Tunru (STAI Hubbulwathan Duri, 2022)
This journal examines the implementation of the National Education System Law Number 20 of 2003 concerning the Right to Get Islamic Religious Education in State Elementary Schools in North Minahasa. The main problem is to know the standardization for implementing Islamic religious education services at two elementary schools (SDN Suwaan and SD Inpres Kawangkoan) and to find out the realization of the right to receive Islamic religious education, mainly in Kalawat District, North Minahasa Regency. This research is field research, using descriptive qualitative research methods with data collection techniques, namely observation, interviews, and documentation. The findings of this study indicate that the standardization of implementing Islamic religious education services at those two schools is to pay attention to the presence or number of students who are Muslim, namely with a minimum ratio of 15 students in one class or in one school as stated in the Regulations. Therefore, the realization of the right to obtain Islamic religious education based on the National Education System Law no. 20 of 2003 at these schools could be realized as it should be. This is because students have not received religious education taught by educators of the same religion because of the unavailability of Islamic religious educators, so that the law has not been implemented properly.